2012
DOI: 10.1074/jbc.m112.395608
|View full text |Cite
|
Sign up to set email alerts
|

The Metalloprotease Meprin β Generates Amino Terminal-truncated Amyloid β Peptide Species

Abstract: Background: Meprin ␤ cleaves the amyloid precursor protein.Results: Meprin ␤-mediated cleavage of the amyloid precursor protein leads to an increase of amyloid ␤ production and to the generation of an N-terminal truncated amyloid ␤ variant. Conclusion: Meprin ␤ can generate N-terminal truncated amyloid ␤ peptides. Significance: Our data indicate that meprin ␤ is a novel protease in amyloid ␤ generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 38 publications
(20 reference statements)
5
99
0
Order By: Relevance
“…This is interesting, because BACE has an acidic pH optimum (35,36) but APP is nevertheless metabolized to Aβ in the presence of bafilomycin A1. This phenomenon, which has been observed by others (37)(38)(39), could result from BACE-like cleavage of APP by cellular proteases that do not require an acidic milieu for activity. Candidate proteases include caspases that may become activated by cathepsins leaked from lysosomes after bafilomycin A1 treatment (40).…”
Section: Discussionmentioning
confidence: 96%
“…This is interesting, because BACE has an acidic pH optimum (35,36) but APP is nevertheless metabolized to Aβ in the presence of bafilomycin A1. This phenomenon, which has been observed by others (37)(38)(39), could result from BACE-like cleavage of APP by cellular proteases that do not require an acidic milieu for activity. Candidate proteases include caspases that may become activated by cathepsins leaked from lysosomes after bafilomycin A1 treatment (40).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, these positions are conserved among physiological substrates (36). An example is APP, which is cleaved by Mβ at the β-secretase site (M 671 -D 672 ; APP residue numbers as subindices according to UniProt P05067) in vivo and in vitro to generate amyloidogenic Aβ42 and Aβ41 peptides (14,15). This process entails that upon Michaelis-complex formation, APP segment D 672 AEFRHDSGYE 682 occupies substrate positions P 1 ′-P 11 ′.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, human meprin β (Mβ) was found to specifically process APP in vivo, which may contribute to Alzheimer's disease (14,15). It was also reported to activate cell-anchored α-secretase ADAM-10 and to be widely expressed in brain, intestine, kidney, and skin (14,(16)(17)(18).…”
mentioning
confidence: 99%
“…1D) (26). Furthermore, cells expressing meprin ␤ produced significant amounts of A␤2-X even in the presence of a BACE1 inhibitor, whereas meprin ␤ inhibition significantly reduced its production (26). Further work has suggested that unlike BACE1, meprin ␤ cleaves APP at the cell surface and may directly compete with ADAM10 in vivo, as indicated by increased sAPP␣ in the soluble fractions derived from meprin ␤ knock-out mice brains (27).…”
Section: -Secretasementioning
confidence: 99%
“…In addition, a concomitant reduction in markers of gliosis, increases in neuronal (Fig. 1D) (26). Furthermore, cells expressing meprin ␤ produced significant amounts of A␤2-X even in the presence of a BACE1 inhibitor, whereas meprin ␤ inhibition significantly reduced its production (26).…”
Section: -Secretasementioning
confidence: 99%